Stent Fracture After Sirolimus-Eluting Stent Implantation. (August 2015) - Ohya, Masanobu; Kadota, Kazushige; Tada, Takeshi; Habara, Seiji; Shimada, Takenobu; Amano, Hidewo; Izawa, Yu; Hyodo, Yusuke; Miyake, Koshi; Otsuru, Suguru; Hasegawa, Daiji; Tanaka, Hiroyuki; et al.
<x xml:space="preserve">Abstract</x> Background— Stent fracture (SF) after sirolimus-eluting stent implantation is reported to be associated with target lesion revascularization (TLR) and stent thrombosis. We aimed to assess the clinical impact of SF at 8 years. Methods and Results— Between 2002 and 2005, 972 patients (1795 lesions) underwent sirolimus-eluting stent implantation and follow-up angiography within 1 year after index procedure. SF, defined as the complete separation of stent segments or stent struts at follow-up angiography, was observed in 105 lesions (5.8%). The study sample comprised 954 patients (1630 lesions), excluding 147 lesions undergoing TLR and 18 patients (18 lesions) who died or in whom stent thrombosis developed within 1 year after sirolimus-eluting stent implantation. The median follow-up duration was 9.1 years (the first and third quarters, 8.7 and 9.4 years). The primary end point was defined as any TLR. The 8-year cumulative rates of adverse events were estimated by Kaplan–Meier methods with P values from log-rank tests. Between patients with and without SF, there were no significant differences in the cumulative rates of all-cause death (23.5% versus 27.6%, P=0.35) and cardiac death (4.7% versus 9.1%, P=0.14), whereas patients with SF had significantly higher cumulative rates in myocardial infarction (10.1% versus 3.3%, P=0.001), very late stent thrombosis (6.8% versus 0.7%, P<0.001), any TLR (38.1% versus 10.8%, P<0.001), and clinically driven TLR (26.2% versus 6.6%, P<0.001). Conclusions— SF after sirolimus-eluting stent implantation was consistently associated with higher rates of adverse cardiac events during the 8-year follow-up.